Comparison of Nyamplung Plant Establishment: Direct Seeding, Bare-root, Blocked Media, and Containerized Seedlings - Dede J. Sudrajat; Nurhasybi Nurhasybi; Eliya Suita (Jurnal Manajemen Hutan Tropika, 2018)
Nyamplung (Calophyllum inophyllum L.), a native multipurpose tree species, produces good general-purpose timber, biodiesel, and medicine. The most widely used method of establishing the species is transplanting nursery-grown containerized seedlings. The research was aimed to compare the success of plant establishment methods, including direct seeding, direct seeding using seed pellet, bare-root seedling, containerized, and blocked media seedlings. Randomized block design with three blocks was set up for evaluation of field performances including seedling survival, height, collar diameter, root development, and biomass at nine months old. The estimated cost based on 1000 target plants in each method was calculated. Seedling grown up on blocked media and containerized media had the highest field performances (survival, growth, and biomass) followed by bare-root seedlings. Direct seeding using seed pellet tended to have better root formation, especially in tap root length, tap root biomass, and bellow-ground biomass. Based on the cost estimation, direct seeding was twice lower compared to transplanting of containerized and blocked media seedlings. However, planting of blocked media and containerized seedlings was more effective in rapidly growth and establishing canopy, but need higher cost. Whereas direct seeding using seed pellet was more cost efficient. Direct seeding using seed pellet was a promising alternative method for plant establishment of nyamplung.